Effects of biochars on the availability of heavy metals to ryegrass in an alkaline contaminated soil. (November 2016) - Zhang, Guixiang; Guo, Xiaofang; Zhao, Zhihua; He, Qiusheng; Wang, Shuifeng; Zhu, Yuen; Yan, Yulong; Liu, Xitao; Sun, Ke; Zhao, Ye; Qian, Tianwei
Abstract: A pot experiment was conducted to investigate the effects of biochars on the availability of heavy metals (Cd, Cu, Mn, Ni, Pb, and Zn) to ryegrass in an alkaline contaminated soil. Biochars only slightly decreased or even increased the availability of heavy metals assesses by chemical extractant (a mixture of 0.05 mol L −1 ethylenediaminetetraacetic acid disodium, 0.01 mol L −1 CaCl2, and 0.1 mol L −1 triethanolamine). The significantly positive correlation between most chemical-extractable heavy metals and the ash content in biochars indicated the positive role of ash in this extraction. Biochars significantly reduced the plant uptake of heavy metals, excluding Mn. The absence of a positive correlation between the chemical-extractable heavy metals and the plant uptake counterparts (except for Mn) indicates that chemical extractability is probably not a reliable indicator to predict the phytoavailability of most heavy metals in alkaline soils treated with biochars. The obviously negative correlation between the plant uptake of heavy metals (except for Mn) and the (O + N)/C and H/C indicates that biochars with more polar groups, which were produced at lower temperatures, had higher efficiency for reducing the phytoavailability of heavy metals. The significantly negative correlations between the plant uptake of Mn and ryegrass biomass indicated the "dilution effect" caused by the improvement of biomass. These observations will be helpful for designing biochars as soil amendments to reduce the availability of heavy metals to plants in soils, especially in alkaline soils. Graphical abstract: Highlights: Effect of biochar on phytoavailability of heavy metal in alkaline soil was studied. Ash in biochar probably had a positive role in chemical extractability of heavy metal. Biochar significantly reduced phytoavailability of most heavy metals to ryegrass. Chemical extractability failed to assess metal phytoavailability in soil with biochar. Biochar produced at lower temperature was recommended for remediation of similar soil. Abstract : Biochars with more polar groups, which were produced at lower temperatures, had higher efficiency for reducing the phytoavailability of heavy metals to ryegrass in an alkaline soil.